2023
DOI: 10.3390/s23041889
|View full text |Cite
|
Sign up to set email alerts
|

Generative Adversarial Network-Based Fault Detection in Semiconductor Equipment with Class-Imbalanced Data

Abstract: This research proposes an application of generative adversarial networks (GANs) to solve the class imbalance problem in the fault detection and classification study of a plasma etching process. Small changes in the equipment part condition of the plasma equipment may cause an equipment fault, resulting in a process anomaly. Thus, fault detection in the semiconductor process is essential for success in advanced process control. Two datasets that assume faults of the mass flow controller (MFC) in equipment compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Another study presented generative adversarial networks (GANs) of deep learning to solve fault detection with imbalanced data in the plasma etching process. It verified the benefits of GANs solving imbalance OES data problems [21]. This study aims to identify the optimal pulse parameters for producing high-quality AlN films.…”
Section: Introductionmentioning
confidence: 70%
“…Another study presented generative adversarial networks (GANs) of deep learning to solve fault detection with imbalanced data in the plasma etching process. It verified the benefits of GANs solving imbalance OES data problems [21]. This study aims to identify the optimal pulse parameters for producing high-quality AlN films.…”
Section: Introductionmentioning
confidence: 70%
“…The target process was silicon etching using SF 6 , O 2 , and Ar gas plasma. Previous studies have shown that small changes in plasma conditions can significantly affect the Si trench etching results for high aspect ratio [19,21,24,25]. Those studies used 20 × 20 mm 2 silicon pattern samples with an SiO 2 etch mask grown on a 300 mm silicon wafer, whereas in this study, 300 mm silicon wafers were used without a mask.…”
Section: Experiments and Data Acquisitionmentioning
confidence: 99%
“…Synthetic Datasets Goodfellow et al ( 2014) proposed GAN as a new generative modeling framework [14] to synthesize new data with the same characteristics from training examples, visually approximating the training data set. Various GANbased methods have been proposed for image synthesis in recent years [15], [16], [17], [18], [19], [20], [21], [22], [23], and [24] with applications spreading rapidly from computer vision and machine learning communities to domain-specific areas such as medical [25] [26], [27], [28], [29], and remote sensing [30], [31], [32] [33], [34], [35], [36], [37], [38], [39], [40], and [41]; industrial process [42], [43], [44], [45], [46], [47], and [48]; and agriculture [49], [50], [51], [52].…”
Section: B Gan (Generative Adversarial Network) To Producementioning
confidence: 99%